Total Polyphenol Intake Estimated by a Modified Folin–Ciocalteu Assay of Urine - Elena Roura; Cristina Andrés‐Lacueva; Ramón Estruch; Rosa M. Lamuela‐Raventós (2006)
Abstract Background: Plant polyphenols have been studied largely because of the possibility that they might underlie the protective effects afforded by fruit and vegetable intake against cancer and other chronic diseases. Measurement of polyphenol content excreted in urine as an indicator of polyphenol consumption may offer a routine screening method that could be used for these pathologies. Methods: Thirty-six healthy volunteers each received 2 interventions, one with a polyphenol-rich food (cocoa beverage) and one with a polyphenol-free food (milk) as a control, in a randomized cross-over design with 1-week intervals. The total polyphenol content excreted in urine during the 6 h after consumption of the test meals was measured by a modified Folin-Ciocalteu assay after sample cleanup by solid-phase extraction. Results: The mean (SD) concentrations of polyphenols excreted in the urine 6 h after consumption of the test meals differed significantly: 140.95 (49.27) mg catechin/g of creatinine after the polyphenol-rich meal vs 90.43 (46.07) mg catechin/g of creatinine after the control meal (P <0.05). Conclusions: This method allows analysis of a large number of samples per day, which is ideal for use in epidemiologic studies and may enable estimation of polyphenol consumption and determination of their possible role in preventing of certain pathologies, such as cancer, cardiovascular and degenerative diseases.